Gli Invisibili: Polizia politica e agenti segreti nell'Ottocento borbonico The Invisibles: Political Police and Secret Agents in the Nineteenth-Century Mezzogiorno - Laura Di Fiore (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2018)
During the nineteenth century, the police control represented, for the European continent, first one of the pivotal components of the international system developed by Metternich and then a function to be reshaped in view of the political crisis due to the events of 1848. In the Kingdom of the Two Sicilies, in the aftermath of the French Decade, the police were the focus of an intense reflection, inclined to rethink it beyond the Napoleonic model, whose outcome was not at all obvious. The issues that emerged in this context concerning the nature and limits of police power were destined to remain, in the following decades, the subject of a debate developed in the broader framework of the Italian peninsula. The revolutionary turmoil crossing the Kingdom, in particular following the 1848 revolutions, nevertheless placed in the foreground the urgency of deploying suitable devices and instruments to make the prevailing task of police control a defense of the status quo. Moreover, facing the global scale of the liberal-democratic threat, the Bourbon police rearranged political surveillance in a transnational sense, resorting to secret agents and spies, but also to consuls and diplomats, on the trail of exiles and conspirators in a European and Mediterranean dimension.